Principles of development - Lewis Wolpert
This book is part of a series entitled Polymeric Foams and is a companion to the volume, Foam Extrusion: Principles and Practices (2000). It addresses new topics such as polymer blends and mechanical properties and develops other topics that have only been overviewed in Foam Extrusion. Written by experts, the book presents the latest research in foam extrusion and foaming polymer blends with a strong focus on polymeric materials interaction in foaming process. Thermoplastic Foam Processing: Principles and Applications gives the reader a clear understanding of the current trends in R & D and an up-to-date review of the current knowledge in thermoplastic foam processing